ResearcHER : the power and potential of research careers for women (Emerald Publishing, 2022)
ResearcHER smashes stereotypes to show you that research is not just conducted by men and women in lab coats or stuck in stuffy offices; researchers are women from diverse geographies, are disabled and able-bodied, are transgender, nonbinary, queer. Researchers look just like you, and you could be one too.